Census of biodiversity in marine caves of the eastern Mediterranean Sea - Gerovasileiou, V.; Chintiroglou, C. C.; Vafidis, D.; Koutsoubas, D.; Sini, M.; Dailianis, T.; Issaris, Y.; Akritopoulou, E.; Dimarchopoulou, D.; Voultsiadou, E. (Mediterranean Marine Science, 2015)
Scientific information on the biodiversity of marine caves in the eastern Mediterranean is limited, especially when considering the extensively studied caves of the north-western and central Mediterranean. Aiming to enhance current knowledge regarding cave communities, this study represents a first assessment of the marine cave biota of the eastern Mediterranean, as defined by the European Union’s Marine Strategy Framework Directive (MSFD). Information retrieved from an extensive overview of relevant scientific documents was combined with original data recorded from 23 marine caves in the north-eastern Mediterranean. Our results report a total of 520 taxa recorded in eastern Mediterranean marine caves to date, the majority of which are sponges, polychaetes, rhodophytes, bivalves, fishes, and gastropods. These include several protected, endemic and alien species. However, not all taxonomic groups from different areas have been equally investigated and future studies are expected to increase the number of endemic and alien species. The observed general trend is that the reported species number is generally related to sampling effort and scientific expertise. The most well-studied marine cave communities in the eastern Mediterranean are those of the Aegean Sea (especially its northern sector), which presented the highest number of species, followed by those of the Levantine. Furthermore, our research in Aegean caves revealed numerous new records for the marine cave fauna of the eastern basin, while several species are reported for the first time in a marine cave habitat. The critical need for further scientific research, monitoring, and conservation of this unique ecosystem was highlighted by (i) the presence of certain species endemic to the eastern Mediterranean coupled with a high proportion of alien species, especially in the Levantine Basin, and (ii) marine cave habitat availability in isolated insular areas of the eastern Mediterranean.